Treatment of Simple Anterior Crossbite with a Removable Appliance in the Permanent Dentition: A Case Report - BEYCAN, KADİR (AVES PRESS LTD, 2016)
This case report presents the treatment of a patient with a simple anterior crossbite using a removable appliance in the permanent dentition. The chief complaint of the 12-year-old female patient was the ugly appearance of her front teeth. She had a symmetrical face with competent lips, dental Class I canine and molar relationships, upper and lower anterior crowding, and an anterior dental crossbite because of a lingually positioned upper left central incisor. The lower left central incisor was labially positioned and was prone to occlusal trauma. Gingival recession on the labial surface of the lower left central incisor was considered to be because of a traumatic occlusion. The patient was on the waiting list for fixed orthodontic treatment; therefore, it was decided to perform removable appliance treatment as soon as possible to correct the crossbite, resolve the crowding, and eliminate the occlusal trauma. The treatment plan included a removable orthodontic appliance with a biteplate and finger springs. At the end of the 5-month treatment, the crossbite was successfully corrected, crowding was resolved, occlusal trauma was eliminated, normal overjet and overbite were achieved, and the smile esthetics significantly improved. In properly selected cases (even in adolescents), with cases involving good and satisfactory patient compliance, correction of a simple anterior crossbite can be successfully achieved using a removable appliance.
Keywords: Anterior crossbite; permanent dentition; removable appliance